Music Makes the World Go Round: The Impact of Musical Training on Non-musical Cognitive Functions—A Review - Benz, Sarah; Sellaro, Roberta; Hommel, Bernhard; Colzato, Lorenza S. (Frontiers in Psychology, 2016)
Musical training is becoming increasingly popular as a topic for scientific research. Here we review the available studies investigating whether and to which degree musical experience generalizes to cognitive functions unrelated to music abilities in healthy humans. In general, it seems that musical training is associated with enhancing effects, even if sometimes only restricted to the auditory domain, on various cognitive functions spanning from executive control to creativity. We conclude that musical engagement may be a useful cognitive training to promote cognitive enhancement, but more research using longitudinal studies and taking into account individual differences is necessary to determine actual benefits.